Is impaired joint attention present in non-clinical individuals with high autistic traits?. Issue 1 (December 2015) - Zhao, Shuo; Uono, Shota; Yoshimura, Sayaka; Toichi, Motomi
Abstract Background Joint attention skills are impaired in individuals with autism spectrum disorder (ASD). Recently, varying degrees of autistic social attention deficit have been detected in the general population. We investigated gaze-triggered attention in individuals with high and low levels of autistic traits under visual–auditory cross-modal conditions, which are more sensitive to social attention deficits than unimodal paradigms. Methods Sixty-six typically developing adults were divided into low- and high-autistic-trait groups according to scores on the autism-spectrum quotient (AQ) questionnaire. We examined gaze-triggered attention under visual–auditory cross-modal conditions. Two sounds (a social voice and a non-social tone) were manipulated as targets to infer the relationship between the cue and the target. Two types of stimulus onset asynchrony (SOA) conditions (a shorter 200-ms SOA and a longer 800-ms SOA) were used to directly test the effect of gaze cues on the detection of a sound target across different temporal intervals. Results Individuals with high autistic traits (high-AQ group) did not differ from those with low autistic traits (low-AQ group) with respect to gaze-triggered attention when voices or tones were used as targets under the shorter SOA condition. In contrast, under the longer SOA condition, gaze-triggered attention was not observed in response to tonal targets among individuals in the high-AQ group, whereas it was observed among individuals in the low-AQ group. The results demonstrated that cross-modal gaze-triggered attention is short-lived in individuals with high autistic traits. Conclusions This finding provides insight into the cross-modal joint attention function among individuals along the autism spectrum from low autistic traits to ASD and may further our understanding of social behaviours among individuals at different places along the autistic trait continuum.